Teachers' Beliefs about Mathematics and Instructional Practices - Lamichhane, Basanta Raj (Saptagandaki Journal, 2017)
This paper deals with the teachers' beliefs about mathematics and relations with their instructional practices based on contemporary literatures and my own experiences. Beliefs have generally been perceived through the personal experiences and interactions with immediate environment and setting. Philosophical beliefs have in the central positions, which are not easily liable to change whereas curricular and pedagogical beliefs seem to be secondary and remain fluids. Two general trends have been observed regarding the relation of teachers’ beliefs about mathematics and instructional practices: conventional pedagogical practices associated with absolutist philosophical, and technically informed curricular beliefs. However, the contemporary/constructivist pedagogical practices are related with fallibilist philosophical beliefs and practical, informed and emancipatory oriented curricular beliefs. The Saptagandaki Journal Vol.8 2017: 14-22